Score based risk assessment of lung cancer and its evaluation for Bangladeshi people - Mukti, Roushney Fatima; Samadder, Pratul Dipta; Emran, Abdullah Al; Ahmed, Farzana; Imran, Iqbal Bin; Malaker, Anyanna; Yeasmin, Sabina (© 2014 Asian Pacific Organization for Cancer Prevention, 2016)
This article was published in the Asian Pacific Journal of Cancer Preventions [© 2014 Asian Pacific Journal of Cancer Prevention] and the definite version is available at : http://dx.doi.org/10.7314/APJCP.2014.15.17.7021 The Journal's website is at: http://koreascience.or.kr/article/ArticleFullRecord.jsp?cn=POCPA9_2014_v15n17_7021